AB0745 Mechanics of early ventricular impairment in systemic sclerosis and the effects of peripheral vasculopathy. (12th June 2018) - Tountas, C.; Bournia, V.-K.; Panopoulos, S.; Gournizakis, A.; Beldekos, D.; Tektonidou, M.G.; Protogerou, A.D.; Sfikakis, P.P.
Abstract : Background: Multiple mechanisms commonly lead to severe cardiac involvement in systemic sclerosis (SSc), an autoimmune disease characterised by microvascular lesions, systemic inflammation and fibrosis. Objectives: To examine the mechanics of right and left ventricles (RV, LV) at the early stage of possible impairment and test the hypothesis that peripheral arterial hemodynamics are associated with an early LV compromise. Methods: Ninety-five asymptomatic SSc patients free of cardiovascular disease (88% women, 53±14 years) and 54 apparently healthy controls matched for age, gender, arterial hypertension, dyslipidaemia, and diabetes mellitus underwent echocardiography, including multilayer speckle-tracking, and tonometry-based pulse wave analysis of the peripheral arteries; 66 SSc patients were prospectively assessed after 32±7 months. Indices of ventricular and arterial structure and function, as well as LV-arterial coupling, were calculated. Results: At baseline, patients presented RV diastolic/systolic impairment, as well as LV remodelling and diastolic/systolic impairment in terms of reduced deformation parameters versus controls. No association was evident between RV and LV strain within individual patients, whereas by multivariate analysis including age, gender and SSc characteristics we found that the global longitudinal strain of RV free wall was associated only with the presence of diffuse skin involvement (b=2.63, p=0.042) and both global longitudinal and circumferential strain of LV were correlated only with disease duration (b=0.14, p=0.001 and b=0.17, p=0.032, respectively). Both RV and LV abnormalities progressed independently during follow-up. Moreover, in the absence of differences in aortic stiffening and LV-arterial coupling between patients and controls, arterial pressure wave reflections assessing small vessel function and/or microcirculation were abnormal in SSc patients and strongly correlated with impaired indices of LV diastolic function and remodelling. Conclusions: These novel findings show the mechanics of RV early impairment in SSc that develops and progresses independently from the concomitant LV impairment, which, in turn, may be influenced by peripheral microvascular abnormalities in the absence of macrovascular damage. Disclosure of Interest: None declared